Gallium Arsenide nanowires for electrode application in solid oxide fuel cell grown using metal organic chemical vapor deposition. (6th April 2017) - Muhammad, R.; Wahab, Y.; Ibrahim, Z.; Deraman, K.; Othaman, Z.; Sakrani, S.
Abstract: Solid oxide fuel cell (SOFC) is a promising efficient device for the direct conversion of the chemical energy into electricity. The development of this highly robust SOFC which operates on a variety of fuels however, requires improvements on the electrodes, where nanoscale engineering is required in order to maximize the number of sites where the electrochemical reactions take place. In this article, we briefly explained the growth of GaAs nanowires on a GaAs substrate as an electrode using metal organic chemical organic vapor deposition (MOCVD). Field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and Conductive atomic force microscopy (CAFM) analysis were carried out as to investigate the structural properties and current–voltage changes in the wires. Results show that nanowires grown are less defect, uniform in composition and with optimum desired diameters. The current–voltage measurement showed it is similar to that of a p–n junction characteristic which is suitable for the SOFC operation. Highlights: Operating temperature of electrode GaAs NW has been done and analyzed between 380 and 600 °C. Current–voltage has been done using conductivity AFM. References were updated.